An assessment of management competencies for primary health care managers in Timor‐Leste. (18th November 2019) - Lopes, Alipio Gusmão; Narattharaksa, Kanida; Siripornpibul, Taweesak; Briggs, David
Summary: Background: This study aims to assess the levels of management competencies of primary health care (PHC) managers in Timor‐Leste. Timor‐Leste is a young country. It has made important improvements in reconstructing its health system since its independence in 2002. However, most managers still learn through their failures, and few studies have described the perceptions of managers in Timor‐Leste. Methods: This study used quantitative methods, using a cross‐sectional survey involving a structured self‐administered questionnaire. The Cochran formula was used in calculating the sample size. The sample included 183 PHC managers in Timor‐Leste. Stratified random sampling was adopted to conduct the survey. The researcher used confirmatory factor analysis (CFA) to confirm the validity and reliability of the tools and create new dimensions. The data were analyzed using the frequency and percentage. Results: This study was initially designed to include seven dimensions, but after confirming it using the CFA, it was reduced to six dimensions. The result of CFA was used. This study found that PHC managers in Timor‐Leste had rated themselves "not competent" in knowing the organization, professionalism in the workplace, problem solving on financial management, and effective leadership and only "competent" in managing human resources and communicating effectively. Conclusion: This study determined that policy makers and stakeholders must give more attention to knowing the organization, professionalism in the workplace, problem solving on financial management, and effective leadership. Managers need to be competent and have various skills to perform managerial functions effectively and efficiently.